Serum lactate levels as a marker of clinical severity in malaria: a prospective observational study - Mehta, Bablu; Lal, Darbari; Behera, Nihar; Vekariya, Grishma (International Journal of Research in Medical Sciences, 2026)
Background: Malaria remains a major cause of morbidity and mortality in tropical countries. Severe malaria is associated with microcirculatory dysfunction, tissue hypoxia, and metabolic derangements. Serum lactate may serve as an early marker of disease severity and prognosis. Objectives were to evaluate serum lactate levels in patients with malaria and assess their association with disease severity and clinical outcomes. Methods: This prospective observational study included 100 adult patients with laboratory-confirmed malaria admitted to a tertiary care hospital. Clinical evaluation and laboratory investigations, including serum lactate estimation at admission, were performed. Disease severity was classified according to WHO criteria. Clinical outcomes were categorized as favorable or adverse. Results: Of the 100 patients, 48% had Plasmodium vivax infection, 42% had Plasmodium falciparum infection, and 10% had mixed infection. Patients with severe malaria had significantly higher serum lactate levels than those with uncomplicated malaria (4.5±1.2 vs. 1.6±0.4 mmol/l; p<0.001). Elevated lactate levels were associated with hypotension, severe anemia, metabolic acidosis, renal dysfunction, altered sensorium, hepatic dysfunction, thrombocytopenia, and hypoglycemia. Adverse outcomes occurred in 45% of patients, including ICU admission (22%), prolonged hospital stay (18%), and mortality (8%). Serum lactate levels were significantly higher in patients with adverse outcomes than in those with favorable outcomes (4.5±1.2 vs. 1.6±0.4 mmol/L; p<0.001). Conclusions: Serum lactate is significantly associated with disease severity and adverse clinical outcomes in malaria. Early lactate estimation may help identify high-risk patients and guide timely management.